Panic Buying Behavior Analysis according to Consumer Income and Product Type during COVID-19 - Brito Junior, Irineu de [UNESP]; Yoshizaki, Hugo Tsugunobu Yoshida; Saraiva, Flaviane Azevedo; Bruno, Nathan de Campos [UNESP]; Silva, Roberto Fray da; Hino, Celso Mitsuo; Aguiar, Larissa Limongi; Ataide, Isabella Marrey Ferreira de (Mdpi, 2023)
In 2020, just before measures were established by governments to minimize the spread of SARS-CoV-2, such as social distancing, quarantine, lockdowns, and internal movement restrictions, people began to buy some products in quantities much superior to their regular needs. This behavior is called panic buying and is a typical human response in times of crisis and uncertainty. This study compares retail sale levels during the period in which panic purchases occurred to the sales levels before and after that period. We analyzed the sales of five groups of products from 144 stores of two major retailers in Sao Paulo, Brazil. Several regression models were used to evaluate the data obtained from demographic information, actual sales, per capita income, and product sales transactions. The results show that sales before, during, and after the panic buying period varied according to the product type and increased according to the average per capita income of each store's influence area. These results may assist policymakers in introducing public policies and managing resources during a crisis that requires social distancing and lockdowns.
Keywords: panic buying; per capita income; consumer behavior; vulnerability; COVID-19